"موقف الشيخ بكر بن عبد الله أبو زيد من فكرة "وحدة الأديان = The position of Shaikh Bakr Abu Zayd from the concept of “Unity of religions” - Abdullah Al-Balwi, Musa; Shehu, Fatmir (IIUM Press, International Islamic University Malaysia, 2018)
تُعد مشكلة هذا البحث في محاولة بيان مفهوم "وحدة الأديان" وايضاح المواقف المتنوعة تجاهها تبعاً للاختلاف في تحديد مفهومها، وتأثيرها في خلط المفاهيم العالمية بالمفاهيم الشرعية، حيث تباينت الرؤى حولها بين معتقد أن "وحدة الأديان" هو نفسه الدعوة إلى مقارنة الأديان والحوار بينها، وبين من هو متبين للموضوع مدرك لضوابطه واحترازاته وفق أسس العقيدة الإسلامية المستنيرة بالكتاب والسنة، وهذا ما سعى الباحث إلى رصده وضبطه. ويهدف هذا البحث إلى إيضاح المعالم والسمات لمنهج الشيخ بكر أبو زيد في معالجته لنازلة "وحدة الأديان" من خلال كتابه: "الإبطال لنظرية الخلط بين دين الإسلام وغيره من الأديان". ويناقش هذا البحث ثلاثة قضايا رئيسية، كالتألي: (1) المقدمة، و(2) التعريف بالحياة الشخصية للشيخ بكر أبو زيد وبكتابه "الإبطال لنظرية الخلط بين دين الإسلام وغيره من الأديان"، (3) بيان موقف الشيخ بكر أبو زيد حول فكرة "وحدة الأديان". ومن أهم نتائج هذا البحث عناية الشيخ بكر بمثل هذه الأفكار الحادثة وتصديه لها، مع بيانه لتناقضات فكرة "وحدة الأديان" مع يقين المسلم بصحة دين الإسلام، وأن دين الإسلام هو الدين الناسخ والخاتم لجميع الأديان التي قبله إلى يوم الدين. وأن فكرة "وحدة الأديان" من المصطلحات الحادثة والمتجددة التي أثارت الكثير من الأسئلة والاستفهامات حول حقيقتها وأهدافها. وأن كثرة الصور والشعـارات المتعـلقة بـها، ما هي إلا إحـدى أنـواع المحاولات الخـدَّاعة، والمثـابرات المـزيفة، للـوصول إلى نشرها وإشاعتها بين الناس. وقد اتبع الباحث في بحثه المنهجين الاستقرائي والتحليلي. ********************************************************* This research attempts to explain the concept of “Unity of Religions” and to clarify various attitudes towards it in accordance with the differentiation in determining its definition and its impact in mixing the global concepts with the legitimate concepts. The views of those who believe that the concept of “Unity of Religions” is the same call for “comparative religion” and “inter-religious dialogue”, differ from the views of those who are aware of the subject and its regulations and precautions based on the principles of Islamic doctrine enlightened by the Book and the Sunnah, and this is what the researcher sought to observe and monitor. The purpose of this research is to clarify the landmarks and features of Shaikh Bakr Abu Zayd’s approach in dealing with the concept of “Unity of Religions” through his book: "Revoking the Theory of Mixing the Religion of Islam with Other Religions". This research discusses three important issues: (1) introduction; (2) informing about the personal life Shaikh Bakr Abu Zayd and his book: “Revoking the Theory of Mixing the Religion of Islam with Other Religions;” and (3) showing Shaikh Bakr Abu Zayd’s position on the concept of “Unity of Religions.” One of the most important results of this research is the attention of Shaikh Bakr to such contemporary concepts and its response to it. He clarifies the contradictions of the concept of “Unity of Religions” with the Muslim’s certainty of the validity of the religion of Islam. The religion of Islam is the seal of all religions before it until the Day of Judgement. The concept of “Unity of Religions” it is among the contemporary renewed terms, which has raised a lot of questions and inquiries about its reality and objectives. Numerous images and slogans related to it are only one of the types of deceiving attempts and false perseverance in order to spread and disseminate it among people. Inductive and analytical methods are used by the researcher in this paper. ********************************************************